Home Country Networks and Foreign Expansion: Evidence from the Venture Capital Industry - Guler, Isin; Guillén, Mauro F. (Academy of Management Journal, 2010)
We propose that home country network advantages shape firms' foreign expansion. We argue that a social status advantage is transferable from one market to another as a signal of quality but that a brokerage advantage is more context-specific and difficult to transfer. Furthermore, the value of network advantages changes as networks evolve. Data on the foreign market entries of 1,010 U.S. venture capital firms provide robust support for the effects of social status. We also find that brokerage reduces foreign entry in the absence of home country partners in a new market and increases it when partners are already operating in that market.